Safety of Endoscopic Sinus Surgery in the Elderly—Are Octogenarian Patients at a Higher Risk?. Issue 1 (January 2022) - Levi, Lirit; Reuven, Yonatan; Ben-Ner, Daniel; Koch, Noam; Gunders-Peleg, Mor; Nachalon, Yuval; Koren, Ilan; Hazan, Alain; Nakache, Gabriel; Reifen, Ella; Soudry, Ethan
Background: Surgeons are often faced with concerns regarding the risks versus benefits of endoscopic sinus surgery (ESS) in elderly patients. Objective: To analyze the risk for complications of ESS in the elderly (age ≥70 years) compared to younger patients, with emphasis on octogenarians. Methods: Retrospective review of medical charts of adult patients who underwent ESS at a tertiary referral center during the years 2014 to 2018. Results: We compared 128 elderly patients with 276 matched younger patients. In the elderly group mean age was 76 years (range, 70-91 years ). Thirty-one elderly patients were 80 years or older. Surgical complications in the elderly patients were 3.9%. Minor complications were 2.3% and major complications were 1.7%. The surgical complications rate was similar in the younger group (8%, P value: .127). Medical complications were observed in 2.3% comparing to 0.7% in younger patients. Interestingly, age, revision surgery, extent and duration of surgery, and modality of anesthesia were not identified as risk factors. Only ischemic heart disease (IHD) was identified as a risk factor for complications in a multivariate analysis in elderly patients. Comparison of elderly patients younger than 80 years with octogenarians revealed no difference in complication rate between these groups. Conclusions: Overall, ESS was found to be a safe procedure in elderly patients compared to younger patients. Octogenarian patients should not be denied upfront surgery. IHD is a risk factor for complications in elderly patients.